Report on the Eleventh Conference on Climate Change and Development in Africa (CCDA–XI) and Outcome statement on priority issues to take climate action forward in Africa. on the theme: Green Growth and Climate Finance Solutions for Africa and the World - Lesolle, David; Murombedzi, James; Nyambe, Harsen; Wanambwa, Leah Naess; Kinyangi, James; Amha, Yosef; Mofor, Linus; Paulos, Mekalia; Muraya, Charles; Rutabingwa, Frank; Demissie, Teferi Dejene; Solomon, Dawit (United Nations Economic Commission for Africa, 2023)
The Climate for Development in Africa (ClimDev-Africa) is a joint initiative of the African Union Commission, the United Nations Economic Commission for Africa, and the African Development Bank, that is conferred the mandate from the African Union Decision Assembly/AU/Dec.134 (VIII) of the 8th Ordinary Session in 2007, to support climate interventions in African countries. The initiative hosts the annual conference on Climate Change and Development in Africa (CCDA). The CCDA is traditionally convened each year, in partnership with the Government of any African Union Member State that hosts the Conference, ahead of the UNFCCC Conference of Parties to the UNFCCC (COP). The annual conference brings together different African stakeholder groups on climate change to discuss key climate change and development challenges facing the continent as well as identify opportunities and solutions. The conference promotes evidence-based and analytically grounded contributions that feed into the African common position meetings in the international discourse on climate change. This year, the ClimDev-Africa partners, in collaboration with the Ministry of Environment, Climate Change & Forestry of the Government of Kenya and with the support of the PanAfrican Climate Justice Alliance (PACJA), propose to convene the eleventh CCDA (CCDA-XI) conference on September 1 – 2, 2023 in Nairobi, as the technical segment of the Africa Climate Summit (ACS) under the ACS overarching theme; “Green Growth and Climate Finance Solutions for Africa and the World”.